Meet me in St. Louis [videorecording (DVD)] - Minnelli, Vincente; Garland, Judy; O'Brien, Margaret, 1937-; Astor, Mary, 1906-1987; Benson, Sally, 1897-1972; Minnelli, Liza; Fricke, John; Martin, Hugh, 1914-2011 (Distributed by Warner Home Video, 2004)
Story of a family at the 1903 World's Fair.